Knowledge and attitude towards pharmacovigilance among healthcare students at a medical college in Nepal - Malla, Bindu; Malla, Komal Prasad; Shrestha, Niranjan; Dhakal, Ganesh; Simangainda, Deependra Man Shrestha; Nepal, Sushil; Dhakal, Madan (International Journal of Basic & Clinical Pharmacology, 2023)
Background: Pharmacovigilance is the science and activities relating to the detection, assessment, understanding, and prevention of adverse drug reactions (ADRs) and any other possible drug-related problems. Under reporting of adverse drugs reactions are the global health problem. The adequate knowledge and skills towards pharmacovigilance and adverse drugs reactions reporting are crucial for the health care students to ensure patients’ medication safety. This study aims to assess the knowledge and attitude of the health care students towards pharmacovigilance and ADRs. Methods: A closed ended, structured, self-administered questionnaire was administered to 204 undergraduate health care students to collect the data. Data were analyzed using SPSS version 21. Non-parametric tests (Mann Whitney U test and Kruskal Wallis test) were used for analysis. Results: Among 204 respondents, the majority of them had a poor knowledge (91.18%) and positive attitude (87.25%) towards Pharmacovigilance. The inter quartile range (median) score of the respondents’ knowledge was 5.0±2.211 and attitude was 27.0±2.88 towards Pharmacovigilance and ADRs reporting. The main reason for under reporting of ADRs was difficulty to decide whether ADR has occurred or not (32.4%) due to the lack of appropriate knowledge and training. There is a poor knowledge and positive attitude towards Pharmacovigilance. Conclusions: Adequate coverage of Pharmacovigilance and ADRs reporting issues should be covered in the curriculum as well as hand on training and workshop should be conducted to increase the knowledge and confidence in detecting, monitoring and reporting ADR in their clinical posting.